Clinical and molecular findings of FRMD7 related congenital nystagmus as adifferential diagnosis of ocular albinism. (4th March 2019) - Michaud, Vincent; Defoort-Dhellemmes, Sabine; Drumare, Isabelle; Pennamen, Perrine; Plaisant, Claudio; Lasseaux, Eulalie; Arveiler, Benoit
ABSTRACT: Background : Congenital nystagmus is one of the most common neuro-ophthalmological disorders. X chromosome-linked forms are associated with pathogenic variants of the GPR143 and FRMD7 genes. Materials and Methods : Patients' DNA was analyzed using a next‐generation sequencing (NGS) panel of genes involved in albinism and related pathologies ( TYR, OCA2, TYRP1, SLC45A2, SLC24A5, C10ORF11, GPR143, SLC38A8, HPS 1 to 10, LYST, MITF, FRMD7 ) Results : We report a 4 generation family with 5 affected members initially referred for molecular diagnosis of ocular albinism. A missense variant of FRMD7 was found in 3 affected cases and one female carrier. We show that the disease in the affected girl is due to skewed inactivation of the X chromosome. Conclusions : By compiling all the published cases we discuss the variable penetrance among females due to different types of mutation and to X-inactivation.